Issues in pain management and Nurses role (2009)
As the healthcare professionals involved in giving bedside care round-the-clock, professional nurses are in a unique position to promote state-of-the-art pain management practices for the health care consumer. Nurses make judgments regarding administration of ordered medications, timing of patient care activities, and also enable patients to make knowledgeable decisions regarding management of their pain. Historically, health care professionals maintained strict control over pain medications in order to protect patients/'clients from deleterious effects of opioid medications, especially with concerns regarding addiction. However, as the health care consumers demanded a more active role in decision-making and as research has shown that fears of addiction were grossly exaggerated, pain rating and approaches to pain management are currently based on patients' self-reports and response to treatment. Potential deleterious effects of pain medications are now weighed against well researched negative effects of uncontrolled pain on patient's well-being, as well as patients' identified goals for pain relief The impetus for this chapter, is to examine the issues on pain management from a contemporary perspective and its implication for nurses role